Efficacy of treatment to relieve mucositis-induced discomfort - (:unkn) unknown (Springer Verlag, 2000)
To determine the efficacy of a mouthwash in relieving mucositis-induced discomfort in patients receiving chemotherapy, 31 (16 male, 15 female) with a mean age of 45 (range 16-80) were given an in-house three-drug (lidocaine, diphenhydramine and sodium bicarbonate in normal saline) mouthwash when they developed mucositis of any severity. The complications were assessed on the CALGB (Cancer and Leukemia Group B) scale. The response to the mouthwash was reported on a self-assessment scale. Patients' response data were analyzed with reference to: (1) relief throughout the duration of mucositis and (2) relief during the worst stage (for each episode) of mucositis. Five patients with fungal, viral or bacterial oral infection were excluded from study. Overall, 4 patients had grade I, 16 patients had grade II, 10 patients had grade III and 1 patient had grade IV mucositis. The average duration of mucositis was 7.9 days (range 3-23 days), and the mean duration of the worst stage of mucositis was 4.81 days (range 2-13 days). The mean mucositis severity score was 1.9 (range 1-4), and the average self-assessment (response) score was 0.81 (range 0-2). The mean mucositis score during the worst stage of mucositis was 2.25 (range 1-4), and the average self- assessment (response) score during the worst stage of mucositis was 0.91 (range 0-2.7). These results suggests that this three-drug mouthwash provides effective symptomatic relief in patients with chemotherapy-induced mucositis.
Keywords: Chemotherapy; Mucositis; Palliation